2003
DOI: 10.1111/j.1708-8208.2003.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Reactions to Abutment Shift: An Experimental Study in Dogs

Abstract: The shift from a healing abutment to a permanent abutment resulted in the establishment of a transmucosal attachment, the dimension and quality of which did not differ from those of the mucosal barrier formed to a permanent abutment placed during a second-stage surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 16 publications
0
54
1
2
Order By: Relevance
“…Jung et al 1996 have demonstrated extensive bone loss around implants with 3 mm long polished neck part. In studies with one-piece implants, which bypass the effect of microgap, bone level was found to establish at the border of smooth-rough surface, regardless the deepness of implant positioning (Abrahamsson et al 2003). Thus it can be concluded that polished implant neck is a valid etiologic factor in crestal bone loss pathogenesis.…”
Section: I31 Ad) Polished Implant Neckmentioning
confidence: 89%
See 2 more Smart Citations
“…Jung et al 1996 have demonstrated extensive bone loss around implants with 3 mm long polished neck part. In studies with one-piece implants, which bypass the effect of microgap, bone level was found to establish at the border of smooth-rough surface, regardless the deepness of implant positioning (Abrahamsson et al 2003). Thus it can be concluded that polished implant neck is a valid etiologic factor in crestal bone loss pathogenesis.…”
Section: I31 Ad) Polished Implant Neckmentioning
confidence: 89%
“…Before permanent placement, the abutment should be cleaned in ultrasonic bath or even autoclaved, as proposed by some authors in order to clean all debris and microorganisms (Brånemark et al 1985). This leakage is responsible for abutment-related inflammatory cell infiltrate formation in soft tissues adjacent to microgap, as described in numerous histological animal studies (Abrahamsson et al 2003;Ericsson et al 1995;. Ericsson et al 1995 termed it "abutment-infiltrated connective tissue" and suggested that its presence shows the reaction of host to the bacterial contamination of inner abutment components.…”
Section: I31 Ac) Microgapmentioning
confidence: 99%
See 1 more Smart Citation
“…En cas d'agression, il cherche à conserver ses dimensions, d' où l'apparition d'une cratérisation à la jonction implant-pilier, le tout favorisé par l' existence d'un microgap, puis par des micromouvements à l'interface pilier-implant après la mise en charge [14]. Abrahamsson et al [15] montrent que le vissage-dé-vissage du pilier, s'il est unique, n'induit pas de remodelage de l' os marginal. En revanche, la répétition de vissage-dévissage sur l'implant induit une résorption osseuse marginale.…”
Section: Caractérisationunclassified
“…Insertion and removal of the abutment has the potential to alter soft tissue levels and this may have an impact on the aesthetic outcome. 5,6 While these findings should be kept in mind and these two materials have been shown to be suitable materials with respect to biocompatibility, the weakness of alumina has been discussed and the grey colour of machined titanium can cause discolouration of the tissues. Figure 23 is an intra-oral view of a titanium abutment made for the restoration in Figures 20 and 21.…”
Section: Biocompatibilitymentioning
confidence: 99%